Grey wolf genomic history reveals a dual ancestry of dogs - Bergström, Anders; Stanton, David W. G.; Taron, Ulrike H.; Frantz, Laurent; Sinding, Mikkel-Holger S.; Ersmark, Erik; Pfrengle, Saskia; Cassatt-Johnstone, Molly; Lebrasseur, Ophélie; Girdland-Flink, Linus; Fernandes, Daniel M.; Ollivier, Morgane; et al. (Nature (London), 2022)
The grey wolf ( Canis lupus ) was the first species to give rise to a domestic population, and they remained widespread throughout the last Ice Age when many other large mammal species went extinct. Little is known, however, about the history and possible extinction of past wolf populations or when and where the wolf progenitors of the present-day dog lineage ( Canis familiaris ) lived 1 – 8 . Here we analysed 72 ancient wolf genomes spanning the last 100,000 years from Europe, Siberia and North America. We found that wolf populations were highly connected throughout the Late Pleistocene, with levels of differentiation an order of magnitude lower than they are today. This population connectivity allowed us to detect natural selection across the time series, including rapid fixation of mutations in the gene IFT88 40,000–30,000 years ago. We show that dogs are overall more closely related to ancient wolves from eastern Eurasia than to those from western Eurasia, suggesting a domestication process in the east. However, we also found that dogs in the Near East and Africa derive up to half of their ancestry from a distinct population related to modern southwest Eurasian wolves, reflecting either an independent domestication process or admixture from local wolves. None of the analysed ancient wolf genomes is a direct match for either of these dog ancestries, meaning that the exact progenitor populations remain to be located. DNA from ancient wolves spanning 100,000 years sheds light on wolves’ evolutionary history and the genomic origin of dogs.